2020
DOI: 10.4049/jimmunol.1900180
|View full text |Cite
|
Sign up to set email alerts
|

Allergin-1 Immunoreceptor Suppresses House Dust Mite–Induced Allergic Airway Inflammation

Abstract: House dust mite (HDM) allergens are leading causes of allergic asthma characterized by Th2 responses. The lung-resident CD11b + dendritic cells (DCs) play a key role in Th2 cell development in HDM-induced allergic asthma. However, the regulatory mechanism of HDM-induced CD11b + DC activation remains incompletely understood. In this study, we demonstrate that mice deficient in an inhibitory immunoreceptor, Allergin-1, showed exacerbated HDM-induced airway eosinophilia and serum IgE elevation. By using bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…While collagen(‐like) molecules are known ligands of LAIR‐1, the ligand of Allergin‐1 is unknown. However, airway hyperresponsiveness and inflammation in response to house dust mites are suppressed by Allergin‐1 on mast cells and lung‐resident CD11b+ dendritic cells, respectively 10,12 . This suggests that ligands for Allergin‐1 are present in lung tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While collagen(‐like) molecules are known ligands of LAIR‐1, the ligand of Allergin‐1 is unknown. However, airway hyperresponsiveness and inflammation in response to house dust mites are suppressed by Allergin‐1 on mast cells and lung‐resident CD11b+ dendritic cells, respectively 10,12 . This suggests that ligands for Allergin‐1 are present in lung tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Allergy inhibitory receptor 1 (Allergin‐1) is an immunoreceptor tyrosine‐based inhibitory motif (ITIM)‐bearing immunoglobulin (Ig)‐like receptor that is primarily expressed on B cells (in humans) and myeloid cells (in humans and mice), including all types of granulocytes 7 . The inhibitory function of Allergin‐1 on mast cells and basophilic granulocytes and its regulatory role in allergic diseases has been demonstrated 8–12 . A potential regulatory function of Allergin‐1 on neutrophilic granulocytes and monocytes has received less scrutiny, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an allergy-induced asthma model, researchers found that when PGE2 production is suppressed, the Th2 cell transcription factor GATA3 was negatively regulated, indicating that PGE2 is required in Th2 cell activation [ 62 ]. PGE2 was also found to induce Tfh cell differentiation in prostate cancer [ 63 ].…”
Section: Prostaglandins In Cd4 + T Cellsmentioning
confidence: 99%
“…Numerous studies have been conducted on HDM-induced airway inflammation in murine models. While most studies failed to mention on the role of IgE or mast cells (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79), a recent study showed that HDM-induced airway inflammation is not dependent on IgE or FcεRI (80). In this Perspective, we will overview fundamental aspects of IgE, IgE receptors, and mechanisms of anti-IgE mAb's function.…”
Section: Introductionmentioning
confidence: 99%